2003
DOI: 10.1103/physrevb.67.104417
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-blende compounds of transition elements with N, P, As, Sb, S, Se, and Te as half-metallic systems

Abstract: We report systematic first-principles calculations for ordered zinc-blende compounds of the transition metal elements V, Cr, Mn with the sp elements N, P, As, Sb, S, Se, Te, motivated by recent fabrication of zinc-blende CrAs, CrSb, and MnAs. They show ferromagnetic half-metallic behavior for a wide range of lattice constants. We discuss the origin and trends of half-metallicity, present the calculated equilibrium lattice constants, and examine the half-metallic behavior of their transition element terminated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
245
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 393 publications
(273 citation statements)
references
References 29 publications
27
245
0
1
Order By: Relevance
“…CrSe) and pnictides (e.g. CrAs) in the zinc-blende or wurtzite structures [58], the diluted magnetic semiconductors (e.g. GaAs or ZnO doped with magnetic transition metal ions) [5,6] and the fully spin polarized Heusler alloys.…”
Section: Dos (States/ev)mentioning
confidence: 99%
“…CrSe) and pnictides (e.g. CrAs) in the zinc-blende or wurtzite structures [58], the diluted magnetic semiconductors (e.g. GaAs or ZnO doped with magnetic transition metal ions) [5,6] and the fully spin polarized Heusler alloys.…”
Section: Dos (States/ev)mentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Atomistic characterization of the different properties is ascribed to e.g., crystal field splitting, electron correlation, and the d bandwidth. Of particular interest in the Heusler-alloys is the Fe-based family, e.g., Fe 2 VAl where Fe antisite can induce emerging phenomena, e.g., a para-to-ferromagnetic phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…An obvious hysteresis loop is observed in the lower field region of M vs H plot confirming a ferromagnetic ordering induced by the Cr doping in ZnTe. ferromagnetic with Curie temperature above room temperature and it plays a key role in the ferromagnetic behavior of ZnTe:Cr films [26][27][28][29]. It is therefore concluded that the presence of zincblende ZnCrTe phase along with CrTe precipitates shall be the reason for the observed ferromagnetic behavior in the low field region at all the measured temperatures 5, 77 and 300 K.…”
Section: Magnetic Moment Measurementsmentioning
confidence: 99%